The number of circulating CD26 expressing cells is decreased in critical COVID‐19 illness. Issue 2 (16th March 2022) - deKay, Joanne T.; May, Teresa L.; Riker, Richard R.; Rud, Jonathan; Gagnon, David J.; Sawyer, Douglas B.; Seder, David B.; Ryzhov, Sergey
Abstract: We evaluated the number of CD26 expressing cells in peripheral blood of patients with COVID‐19 within 72 h of admission and on day 4 and day 7 after enrollment. The majority of CD26 expressing cells were presented by CD3 + CD4 + lymphocytes. A low number of CD26 expressing cells were found to be associated with critical‐severity COVID‐19 disease. Conversely, increasing numbers of CD26 expressing T cells over the first week of standard treatment was associated with good outcomes. Clinically, the number of circulating CD26 cells might be a marker of recovery or the therapeutic efficacy of anti‐COVID‐19 treatment. New therapies aimed at preserving and increasing the level of CD26 expressing T cells may prove useful in the treatment of COVID‐19 disease.